Respuesta :
Part 1) we have
[tex]y=-3x+6[/tex] ------> equation A
[tex]y=9[/tex] ------> equation B
Equate equation A and equation B
[tex]9=-3x+6[/tex]
Solve for x
[tex]3x=6-9[/tex]
[tex]x=-3/3=-1[/tex]
the solution is the point [tex](-1,9)[/tex]
therefore
the answer part 1) is the option C
[tex](-1,9)[/tex]
Part 2) we have
[tex]y=\frac{2}{3}x+3[/tex] ------> equation A
[tex]x=-2[/tex] ------> equation B
Substitute equation B in equation A
[tex]y=\frac{2}{3}*(-2)+3[/tex]
[tex]y=-\frac{4}{3}+3[/tex]
[tex]y=\frac{5}{3}[/tex]
the solution is the point [tex](-2,\frac{5}{3})[/tex]
therefore
the answer Part 2) is the option B
[tex](-2,\frac{5}{3})[/tex]
Part 3) we have
[tex]y=\frac{1}{3}x-10[/tex] ------> equation A
[tex]2x+y=4[/tex] ------> equation B
Substitute equation A in equation B
[tex]2x+\frac{1}{3}x-10=4[/tex]
[tex]\frac{7}{3}x=14[/tex]
[tex]x=14*3/7=6[/tex]
Find the value of y
[tex]y=\frac{1}{3}x-10[/tex]
[tex]y=\frac{1}{3}*6-10=-8[/tex]
the solution is the point [tex](6,-8)[/tex]
therefore
the answer Part 3) is the option C
[tex](6,-8)[/tex]
Part 4) we have
[tex]x-y=7[/tex] ------> equation A
[tex]3x-2y=8[/tex] ------> equation B
Step 1
Isolate the variable x in the equation A
[tex]x=y+7[/tex] -------> new equation A
Step 2
Substitute the new equation A in the equation B
[tex]3[y+7]-2y=8[/tex]
Step 3
Solve for y
[tex]3y+21-2y=8[/tex] ------> In this step Ernesto make the first error
Step 4
Combine like terms in the left side
[tex]y+21=8[/tex]
Step 5
Subtract [tex]21[/tex] both sides
[tex]y+21-21=8-21[/tex]
[tex]y=-13[/tex]
therefore
the answer Part 4) is the option C
Step 3